High density monolayers of plasmid protein on latex particles: experiments and theoretical modeling. (20th April 2015) - Kujda, Marta; Adamczyk, Zbigniew; Cieśla, Michał; Adamczyk, Małgorzata
Abstract: Monolayers obtained by adsorption of the plasmid protein KfrA on negatively charged polystyrene latex particles under diffusion-controlled conditions at pH 3.5 were interpreted in terms of the random sequential adsorption (RSA) model. A quantitative agreement of the theoretical results derived from these calculations with experimental data was attained for the ionic strength from 0.15 up to 10 −2  M. This confirmed the adsorption mechanism of KfrA molecules on latex in the form of tetramers up to 10 −2  M. On the other hand, for the ionic strength of 10 −3  M the experimental coverage agreed with theoretical predictions under the assumption that screening of electrostatic interaction is enhanced by the presence of counterions and negatively charged polymer chains stemming from latex particles.